Teknologi, Kerjasama Pemerintah, dan Kurikulum Holistik: Peran Gereja Terhadap Pendidikan Agama Kristen Bagi Kaum Muda - Tarisih Tarisih; Sutrisno Sutrisno (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2022)
The Church has a major role to play in Christian Education for all members of its congregation, including youth. Youth as successors need to be directed, guided and nurtured so as to become mature disciples of Christ in the faith. But the fact is that the church does not fully think seriously and responsibly about Christian Religious Education, especially for youth. Para leaders have failed in setting the goals of Christian Education for youth. Routine tasks have seized the minds of leaders so as not to have the opportunity to think of earnest and planned coaching within the congregation. Answering these problems, the author raised the topic of research on